Choice Constructions of Indonesian Muslimah in Purchasing Halal Cosmetics - Rishan Adha; Selva Selva (Universitas Muhammadiyah Mataram, 2018)
Cosmetic choice for Muslimah is not as simple as we think because it relates to the looks, aesthetics, exposures, and hopes. This study aimed to determine the construction of Muslimah choice in the purchase of cosmetics. The study was conducted by using direct experiments to Muslimah. The experiments were conducted in a controlled environment, where the female respondents were divided into nine groups, with three levels of income and three levels of knowledge about halal cosmetics. This procedure results in more accurate measurements because the variables are controlled by the researchers. The results indicate that there is difference of consumer choice construction between knowledge level and income level. The variable of knowledge level gives a better influence in purchasing decision of halal cosmetics product compared with variable of income level. Different treatments in the provision of halal product information tend to influence consumer purchasing decisions with lower income levels compared with high income consumers.